Experimental study on the tensile and compressive properties of local bamboo fiber polyester composites with varying fiber species and resin ratios - Adlie, Taufan Arif; Arif, Zainal; Kamil, Syahiir; Maidin, Maidin; Hasmi, Farhan; Rizal, Teuku Azuar (Politeknik Negeri Lhokseumawe, 2025)
In response to the growing demand for eco-friendly materials, natural fibers have gained increasing attention as renewable alternatives for automotive and structural materials. Despite extensive research, the mechanical performance of locally sourced bamboo species from Langsa, Aceh, including Gigantochloa apus (apus), Bambusa vulgaris (yellow), and Bambusa blumeana (thorn) remains largely unexplored. This study investigates the tensile and compressive properties of composites reinforced with these three bamboo species. The composites were fabricated using the hand lay-up method using BTQN 157 polyester resin and varying resin-to-fiber ratios of 60:40, 70:30, and 80:20. Mechanical tests were conducted in accordance with ASTM standards to evaluate the influence of bamboo species and fiber composition. Three specimens were tested for each composition, and the results were averaged to ensure data reliability. The results show that both bamboo type and resin fiber ratio significantly affect mechanical performance. The thorn bamboo composite at a 60:40 resin-to-fiber ratio exhibited the highest tensile strength of 81.94 MPa and compressive strength of 9.11 MPa. A 29.67% increase in tensile strength was achieved when varying the resin-to-fiber ratio from 80:20 to 60:40 for yellow bamboo, while a 28.93% improvement was observed across different species. Similarly, a 44.40% rise in compressive strength occurred for apus bamboo composites when the ratio changed from 80:20 to 60:40, and a 54.68% enhancement was recorded across species. These findings confirm that Langsa’s local bamboo, particularly B. blumeana at a 60:40 ratio, offers strong, lightweight, and sustainable reinforcement potential for next-generation composite materials.